The Impact of Spending on Research and Development on the Global Patent Index for a Sample of Developed Countries for the Period 2007-2021 - Bushra Abdulbari Ahmed; Aymen Ajina (Migration Letters, 2023)
The study aims to identify, measure and analyze indicators of spending on research, development and patents for the period (2007-2021) for high-income countries that include (the United States of America, Britain, Japan, Germany, France, Sweden, Canada). The study relied on the standard analysis method. While the study reached a number of results, the most important of which are: the existence of a direct and significant relationship at the level of (1%) between (X1), which represents spending on research and development, and (Y), which represents patents, and that increasing (X1) by (1%) will lead to an increase in ( Y) by (0.138%) in high-income countries, in addition to the existence of a direct and significant relationship at the level of (1%) between (X2), which is represented by researchers working in research and development, and (Y), which is represented by patents, and that an increase in (X2) by ( 1%) leads to an increase in (Y) by (0.698%) in high-income countries. It also found that there is a direct and significant relationship at the level of (1%) between (X3), which is represented by technicians working in research and development, and (Y), which is represented by patents. An increase in (X3) by (1%) will lead to an increase in (Y), which is represented by patents, by (0.229%) in high-income countries. While the study recommended working to increase the allocations allocated to scientific research and technological development from the national income, allocating a percentage of foreign grants and aid for research and scientific purposes, encouraging the beneficiary sectors to contribute to financing research and development projects, and creating a balanced and stable financial system for scientific research, and its success depends on the provision of sufficient financial allocations, so it must The government should allocate a separate budget for research, development and patenting, on the basis of which the winning scientific projects will be funded in competitions to choose the best research project.